A Review Into the Insights of the Role of Endothelial Progenitor Cells on Bone Biology - Shi, Henglei; Zhao, Zhenchen; Jiang, Weidong; Zhu, Peiqi; Zhou, Nuo; Huang, Xuanping (Frontiers in Cell and Developmental Biology, 2022)
In addition to its important transport functions, the skeletal system is involved in complex biological activities for the regulation of blood vessels. Endothelial progenitor cells (EPCs), as stem cells of endothelial cells (ECs), possess an effective proliferative capacity and a powerful angiogenic capacity prior to their differentiation. They demonstrate synergistic effects to promote bone regeneration and vascularization more effectively by co-culturing with multiple cells. EPCs demonstrate a significant therapeutic potential for the treatment of various bone diseases by secreting a combination of growth factors, regulating cellular functions, and promoting bone regeneration. In this review, we retrospect the definition and properties of EPCs, their interaction with mesenchymal stem cells, ECs, smooth muscle cells, and immune cells in bone regeneration, vascularization, and immunity, summarizing their mechanism of action and contribution to bone biology. Additionally, we generalized their role and potential mechanisms in the treatment of various bone diseases, possibly indicating their clinical application.